Kommos Conservancy (2011)
[Dt.:] Die Webseite behandelt die minoische Hafenstadt Kommos, insbesondere die Chronologie des Ortes und die Geschichte der Grabungsaktivitäten. Die Texte werden mit zahlreichen Zeichungen und Abbildungen ergänzt. Ein Schwerpunkt ist die Konservierung und Erhaltung der archäologischen Stätte. Angeboten werden Grabungsberichte und Blogs mit aktuellen Themen. - [Engl.:] The website is focussing on the minoan harbour town of Kommos. It provides information about the history and chronology of the site as well as the history of the excavations. An important aspect is the conservation and preservation of the minoan site. The website offers reports and web logs with current information.